Proses Produksi Tempe Ditinjau Dari Ekonomi Islam (Studi Komperatif Home Industry Desa Pait Kecamatan Siwalan Kabupaten Pekalongan) (Sahmiyya: Jurnal Ekonomi dan Bisnis, 2022)
in terms of Islamic economics and the comparative process of home industry tempeh production by Mr. Saiful and Mr. Bambang in Pait Village, Siwalan District. This study uses a qualitative approach with data collection techniques in the form of observation, interviews and documentation. The analysis technique is reducing data, presenting data, and drawing conclusions. From the results of the study, it was found that the tempe production process belonging to Mr. Saiful and Mr. Bambang was in accordance with the provisions in producing tempeh, even the boiling process was carried out twice so that the tempe was able to last longer. An Islamic economic review of the tempe production process, namely the home industry owned by Mr. Saiful and Mr. Bambang, has been carried out well and in line with the principles of production in Islam, the home industry of Mr. Saiful and Mr. Bambang in the waste disposal process that does not pay attention to the surrounding environment, causing pollution. environment. In terms of tempeh production, the boiling process is only done twice so that the tempeh produced can last up to 2-3 days. In terms of working time, employees work until late at night. And in terms of waste disposal, the rest of the tempeh production process is just thrown away without any prior handling, so that it pollutes the environment.